(untitled) (Journal of Engineering, 2010)
The present research is concerned with studying of the drag force on two spheres moving side by side and in line in non-Newtonian liquid. Polyacryamide (PAA) solution with different concentrations (0.01, 0.03, 0.05 and 0.07)% by weight and water is used for comparison for obtaining the effect of fluid properties on the drag force. Different types of spheres stainless steel, glass and plastic with different sizes and densities were used. Within the considered range of power law index (0.6 - 1), and generated Reynolds number (1.1 -75) in power law fluid and Reynolds number (100 - 1000) for water it was found the drag coefficient increases with increasing the power law index for constant generated Reynolds number and the drag force increases with fluid density increases but it decreases with the sphere density increases.